2006
DOI: 10.1097/01.ccm.0000236546.98861.25
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial of the role of weaning predictors in clinical decision making*

Abstract: Including a weaning predictor (f/Vt) in a protocol prolonged weaning time. In addition, the predictor did not confer survival benefit or reduce the incidence of extubation failure or tracheostomy. The results of this study indicate that f/Vt should not be used routinely in weaning decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
89
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 18 publications
2
89
0
6
Order By: Relevance
“…29 During the SBT the RSBI was also found to stay within the normal range even though the repeated measurements in the esophageal pressure swings showed an increase in respiratory effort and weaning failure. 30 In a recent study, 31 the use of the RSBI did not improve weaning outcome, and it delayed weaning for 2-3 days. Muscle fatigue during an SBT is a complex process that obviously cannot be well predicted based solely on respiratory rate and V T .…”
Section: Discussionmentioning
confidence: 99%
“…29 During the SBT the RSBI was also found to stay within the normal range even though the repeated measurements in the esophageal pressure swings showed an increase in respiratory effort and weaning failure. 30 In a recent study, 31 the use of the RSBI did not improve weaning outcome, and it delayed weaning for 2-3 days. Muscle fatigue during an SBT is a complex process that obviously cannot be well predicted based solely on respiratory rate and V T .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated the importance of this result in the evolution of patients [5,12,13,[18][19][20]24,28]. When compared to the first intubation, reintubation increased eight times the risk of pneumonia and from 6 to 12 times the risk of death, being considered an independent predictor of mortality [13,14,19,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The daily assessment of the weaning parameters held in the experimental group has been described in the literature as one of the factors responsible for good performance observed using the protocol of SBT [4, 13,[16][17][18]31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations